Pengembangan Budaya Sekolah Berprestasi: Penanaman Nilai Etos Berprestasi - Pratiwi, Ageng; Roesminingsih, Erny; Karwanto, Karwanto (Jurnal Ilmiah Mandala Education (JIME), 2021)
Senior High School Muhammdiyah 10 Surabaya is a school that dares to make a different curriculum from Diknas. It was rejected because it did not fit the existing curriculum. In its first year, the school receives two classes of students. This achievement soared in the second year. Second year there are five classes. The curriculum used at Senior High School Muhammadiyah 10 Surabaya is called "Talent Executive School." This study aims to find out the development of outstanding school culture at Senior High School Muhammadiyah 10 Surabaya, also describe the form of outstanding school culture, the process of planting values and ethos of achievement to students and knowing the implications of the development of outstanding school culture at Senior High School Muhammadiyah 10 Surabaya. Although the facilities and infrastructure at Senior High School Muhammadiyah 10 Surabaya have limitations but they are able to continue to develop the potential and ethos of interpreting in the academic and non-academic fields. So it becomes an attraction for researchers to conduct a researcher in the school with a different school style than usual. This study uses a qualitative descriptive approach. Data collection using observation techniques, interviews and documentation. The planting of values and ethos of achievement in students is carried out through school orientation activities, learning process, learning evaluation, extracurricular, achievement awards, love for alma mater, teacher conscientiousness, cooperation with parents of students and planting an outstanding culture. The results showed that the school culture developed at Senior High School Muhammadiyah 10 Surabaya is through educational programs and potential interests including archery, futsal, athletics, pencak silat, archery, music, hockey, dance and others.